Pemberdayaan Masyarakat Melalui Pelatihan Ekonomi Kreatif dalam Mewujudkan Kemandirian Masyarakat di Desa Jayi Kecamatan Sukahaji Kabupaten Majalengka - Asep Saepudin; Iip Saripah; Yusmanto Yusmanto; Jaenal Mutakin; Ani Rindiani (LPPM Universitas Koperasi Indonesia, 2023)
Community development (community development) as a national development strategy in the framework of empowerment (empowerment community, is an important thing that aims to foster community self-reliance in utilizing its potential so that it is able to have the ability to adapt according to the development of the times. For that, empowerment) is a process of social action carried out by individuals, families, groups, communities, and companion organizations in the context of achieving the human development index (Human Development Index) quality. Based on this line of thinking, a community empowerment approach is needed through creative economy training for members of the farming community to support the acceleration of increasing community income, especially in Jayi Village, Kec. Sukahaji, Kab. Majalengka. This training activity is one of the community service programs conducted by community study program lecturers and students for farmers through the stages of preparation, planning, implementation, evaluation, and reporting. The end result of the training activities is an increase in community awareness about the problems they face and their potential so that the readiness of the surrounding community to receive educational interventions appears (education intervention) in order to increase knowledge (cognitive), attitude (affective) and skills (skills) community members as training participants.